1982
DOI: 10.1128/jcm.15.3.408-415.1982
|View full text |Cite
|
Sign up to set email alerts
|

Carpeting in hospitals: an epidemiological evaluation

Abstract: Epidemiological and microbiological studies were conducted in a hospital room with carpet (CR) and in one with carpet (NCR). Microbiological profiles were determined with specimens obtained from patients admitted to these rooms. Patient records were reviewed to note infection status and other case identities. Eleven-millimeter cylindrical core samples of carpet were obtained, and swab template techniques were used on the bare floor for subsequent enumeration and identification of contaminating microorganisms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
2

Year Published

1989
1989
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 8 publications
0
41
2
Order By: Relevance
“…According to the authors, the proportion of fluorescent in total airborne particle concentration increased during walking, in comparison to the times when the room was vacant. An earlier study reported by Anderson et al52 associated high levels of microbial contamination with carpets in patients' rooms. The authors conducted epidemiological and microbiological studies in a hospital rooms with and without carpet.…”
mentioning
confidence: 93%
“…According to the authors, the proportion of fluorescent in total airborne particle concentration increased during walking, in comparison to the times when the room was vacant. An earlier study reported by Anderson et al52 associated high levels of microbial contamination with carpets in patients' rooms. The authors conducted epidemiological and microbiological studies in a hospital rooms with and without carpet.…”
mentioning
confidence: 93%
“…An additional seven articles which met the selection criteria were identified through bibliographical search number of persons and person movement in the operating room [13], and presence of dirt (either soil or water) in hospital areas [14]. Carpets also yielded higher microbial concentrations per square inch compared to bare floors in a paediatric patient's room [15]. Experimental studies investigated walking over contaminated flooring (two studies) or floor cleaning to prevent infection.…”
Section: Resultsmentioning
confidence: 99%
“…There is limited research comparing the air above carpeted areas and hard flooring with respect to concentrations of microorganisms, and the findings are conflicting. Anderson et al (1982) found higher concentrations above carpeted areas, whereas Harris (2000) reported higher particulate concentrations above hard flooring.…”
Section: Environmental Approaches To Reduce Contact-spread Infectionsmentioning
confidence: 97%
“…Automated technology has also been examined for its impact on hand-washing compliance for soap-and-water sinks and alcohol-based hand-rub dispensers. (Anderson et al, 1982;Skoutelis et al, 1994) and furniture coverings (Lankford et al, 2006;Noskin et al, 2000) as they relate to environmental contamination in healthcare settings. The use of carpet can be a controversial issue.…”
Section: Environmental Approaches To Reduce Contact-spread Infectionsmentioning
confidence: 99%